SIGNIFICANCE OF THE PREVENTIVE ULTRASOUND DIAGNOSTICS IN THE EARLY DETECTION OF RARE AND AGGRESSIVE THYROID CARCINOMAS – CASE REPORT - Jovanović, Milica; Jovanović, Predrag; Milinković, Marija; Dunđerović, Duško; Jovanović, Ljubiša (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Medullary thyroid carcinoma (MTC) is an aggressive tumor associated with a significantly poorer prognosis compared to other types of thyroid cancer. Doppler ultrasound and familiarity with the Thyroid Imaging Reporting and Data System (TIRADS) nodule classification are essential. Objective: This case highlights the significance of precise ultrasound imaging, crucial for early detection and subsequent management of such aggressive disease.Case report: We describe the case of a 31-year-old woman who underwent systemic ultrasound imaging. Upon ultrasound examination, a 5 mm x 4 mm x 3 mm hypoechoic, ill-defined solid nodule with echogenic foci (TIRADS 4, score 6) was identified in the mid portion of the left thyroid lobe. Given the suspicious ultrasound features, the location of the nodule, and the elevated serum calcitonin level, the micronodule raised concerns for malignancy, particularly suggesting medullary thyroid microcarcinoma. The patient underwent thyroidectomy, and histopathological analysis confirmed the diagnosis. The histopathology report described a small white nodule (5 mm) in the left lobe. There was no remarkable necrosis, and amyloid deposits were inconspicuous. Lymphovascular invasion was not observed, and mitoses were rare. The tumor stage was T1 (pTNM), and no distant metastases were found. C-cell hyperplasia was noted around the tumor. Immunohistochemical analysis showed positive reactions for calcitonin, chromogranin, and mCEA. The proliferative index was low, approximately 4%. After surgery, serum calcitonin levels decreased. Three years after the surgery, the patient is in good general condition and is under regular monitoring. In the meantime, the patient has become a mother.Conclusion: Early detection and treatment of micro-MTC are crucial, as these tumors have the potential for aggressive behavior. Adequate ultrasound imaging assessment could significantly improve the prognosis and outcome for these patients.
Keywords: ultrasound imaging; thyroid nodule; micro-medullary carcinoma